High Political Costs : Stimulan Ijon Politik Dalam Pilkada Di Kalimantan Timur Tahun 2018 - Ratna Sari, Yunita (Bestuurskunde: Journal of Governmental Studies, 2024)
This study examines the misuse of private political donations in the 2018 regional head elections in East Kalimantan. The high political cost of patron-client relationships, where entrepreneurs act as patrons and candidates act as clients, motivates this study. The study aims to investigate political influence in the 2018 regional head elections in East Kalimantan. It employes a literature review, utilizing secondary data from journals, national survey results, and government publications relevant to the research problem. The findings indicate that concerning the issuance of mining business permits (IUP), there is political influence in the regional head elections in East Kalimantan. In 2017, the number of IUP were 1,194. This number increased to 1,404 from 2018 to 2020. Out of these, 428 IUPs have not yet been certified as Clean and Clear (C n C), and 160 are classified as illegal mining.